Expeditious, Mild and Solvent Free Synthesis of Bis(indolyl)methanes, Using a Mixture of Phosphorus Pentoxide in Methanesulphonic Acid - Amulrao U. Borse; Mahesh N. Patil; Nilesh L. Patil (E-Journal of Chemistry)
Highly rapid and efficient synthesis of Bis(indolyl)methanes has been developed by using a mixture of phosphorus pentoxide in methanesulphonic acid (Eaton’s reagent) at ambient temperature under solvent free condition.